Introduction to ultrafast phenomena : from femtosecond magnetism to high-harmonic generation /: from femtosecond magnetism to high-harmonic generation. (2020) - Zhang, Guo-ping; Lefkidis, Georgios; Murakami, Mitsuko; Hübner, Wolfgang; George, Thomas F, 1947-
No abstract available